Organic farming and commercialization of fruits and vegetables in Makueni County, Kenya - Induli, Irene; Wanyama, Rosina; Odongo, Nicanor; Akingbemisilu, Tosin; Termote, Celine (2024)
➢Agriculture accounts for 20% the Kenya’s Gross Domestic Product (GDP). ➢Approximately 7.5 million smallholder farmers in Kenya. ➢>70% from the rural population. ➢Increased demand for food due to increased population. ➢Food safety knowledge is essential to encourage choice and consumption of safe nutritious foods. ➢Farmer empowerment with knowledge and skills on sustainable safe production.